Robotics in primary school in the opinion of prospective and in-service teachers. A comparison study - Morze, N.; Smyrnova-Trybulska, E.; Zuziak, W.; Kommers, Piet; Gladun, M. (Inderscience Publishers, 2017)
Copyright Â© 2017 Inderscience Enterprises Ltd. This article Describes Some Issues Concerning The Use Of Robots In primary school as an object and subject of learning. The authors conclude, based on an analysis of earlier research as well as their own study, that educational robots can stimulate learners' learning motivation. Compared with other media, programmable bricks provide children with the opportunity to create their own products and, through this process, to express creative thinking. Studies have found that learning robotics or integrating programming bricks into courses can help to develop students' problem-solving abilities and enhance their learning performance. Besides, an analysis is presented of basic legal regulations in this matter, primary school curricula as well as some results of a survey conducted in Poland and Ukraine among in-service teachers and prospective teachers.